2010
DOI: 10.3109/17453674.2010.525196
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of thromboembolic complications after fast-track hip and knee arthroplasty

Abstract: Background and purposePharmacological prophylaxis can reduce the risk of deep venous thrombosis (DVT), pulmonary embolism (PE), and death, and it is recommended 10–35 days after total hip arthroplasty (THA) and at least 10 days after total knee arthroplasty (TKA). However, early mobilization might also reduce the risk of DVT and thereby the need for prolonged prophylaxis, but this has not been considered in the previous literature. Here we report our results with short-duration pharmacological prophylaxis comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 43 publications
(57 reference statements)
7
112
1
4
Order By: Relevance
“…6 This has obvious limitations because of important changes in surgical care, including changes in operative technique, earlier ambulation, and earlier discharge that have had an impact on rates of thrombosis and bleeding. For instance, although the average length of stay after HFS in the 1960s was 35 days, 7 current averages of 3.2 days have been reported in a large cohort after arthroplasties, 8 and early mobilization starts at 2 to 4 h after surgery. 8 Randomized controlled trial (RCT) data typically showed a symptomatic VTE event rate of 15% to 30% without prophylaxis prior to 1980, 6,[9][10][11][12] and observational data suggest a further drop from around 5% to 1% to 2% in the years from 1989 to 2001.…”
Section: Baseline Risk For Vtementioning
confidence: 99%
See 1 more Smart Citation
“…6 This has obvious limitations because of important changes in surgical care, including changes in operative technique, earlier ambulation, and earlier discharge that have had an impact on rates of thrombosis and bleeding. For instance, although the average length of stay after HFS in the 1960s was 35 days, 7 current averages of 3.2 days have been reported in a large cohort after arthroplasties, 8 and early mobilization starts at 2 to 4 h after surgery. 8 Randomized controlled trial (RCT) data typically showed a symptomatic VTE event rate of 15% to 30% without prophylaxis prior to 1980, 6,[9][10][11][12] and observational data suggest a further drop from around 5% to 1% to 2% in the years from 1989 to 2001.…”
Section: Baseline Risk For Vtementioning
confidence: 99%
“…For instance, although the average length of stay after HFS in the 1960s was 35 days, 7 current averages of 3.2 days have been reported in a large cohort after arthroplasties, 8 and early mobilization starts at 2 to 4 h after surgery. 8 Randomized controlled trial (RCT) data typically showed a symptomatic VTE event rate of 15% to 30% without prophylaxis prior to 1980, 6,[9][10][11][12] and observational data suggest a further drop from around 5% to 1% to 2% in the years from 1989 to 2001. 13 In recent years, there have been no large placebo controlled trials, and we did not identify any large, well-designed cohort studies to provide a baseline risk relevant to current practice.…”
Section: Baseline Risk For Vtementioning
confidence: 99%
“…Husted с соавторами также исследовали час-тоту встречаемости тромбоэмболических ослож-нений при ускоренной реабилитации [25]. В про-спективном когортном исследовании оценивалось влияние на показатели смертности кратковре-менной фармакологической тромбопрофилакти-ки Тэла и ТГВ в сочетании с ранней мобилиза-цией и короткой госпитализацией.…”
Section: таблица/unclassified
“…Наряду с ранней активизацией ис-пользуются пневмокомпрессия нижних конечно-стей и различные варианты антикоагулянтов. Наря-ду с парентеральными препаратами (низкомолеку-лярные гепарины и фондапарнукс натрия) в послед-нее время стали применять пероральные препараты, не требующие лабораторного мониторинга, -даби-гатрана этексилат (прадакса) и ривароксоабан (кса-релто), что обеспечивает комфорт больным и их большую мобильность [4,12].…”
Section: предоперационная стратегияunclassified